Transformation of Islamic Religious Education Through Technology - Rahman Selfara; Muhammad Al-Fatur; Raju (AIQU: Journal Multidiscipliner of Science, 2025)
This study explores the transformation of Islamic Religious Education (PAI) learning through the integration of technology at Madrasah Aliyah Negeri 1 Buton Tengah. In response to the growing demand for digital adaptation in education, this research aims to investigate the processes, challenges, and strategies implemented by educators in incorporating technology into PAI instruction. Utilizing a qualitative approach with data collected through interviews and documentation, the findings reveal that technological integration significantly enhances student engagement and comprehension of religious values. However, educators face various obstacles, including limited digital infrastructure, low digital literacy, and the scarcity of contextually appropriate Islamic digital content. Despite these challenges, teachers have adopted adaptive strategies such as utilizing simple but effective platforms like WhatsApp, Google Classroom, and Islamic-themed multimedia content. The study concludes that while technology acts as a catalyst for educational innovation, its effectiveness in religious education depends on the preparedness of teachers and institutional support. This research contributes to the growing body of literature on digital transformation in Islamic education by highlighting context-specific practices and offering insights for policy development and teacher training. It underscores the importance of aligning technological tools with religious pedagogical goals to ensure meaningful and transformative learning experiences for students in the digital era.